Transnational Cyber Offenses: Overcoming Jurisdictional Challenges - Perloff-Giles, Alexandra (2018)
In his 1996 Declaration of the Independence of Cyber Space, cyber activist (and former Grateful Dead lyricist) John Perry Barlow vividly described the Internet as a place beyond national borders: Governments of the Industrial World, you weary giants of flesh and steel, ... I declare the global social space we are building to be naturally independent of the tyrannies you seek to impose on us. You have no moral right to rule us nor do you possess any methods of enforcement we have true reason to fear. ... Cyberspac